THE EFFECT OF ACTIVITIES CHANGES IN TOURISM VILLAGE ON INHABITANT’S SENSE OF PLACE - Ramadhani, Annisa Nur (Border: Jurnal Arsitektur, 2019)
Kampung Improvement Program in Surabaya is a program that focus on improving housing and settlements based on sustainable development. One of them is by the existence of thematic tourism kampung development that has cultural values both tangible and intangible. The development of this tourism kampung has a positive goal to improve the socio-economic welfare of the village community. But on the other hand, there was a change in the function and meaning of the kampung from a settlement system with low social accessibility to an open settlement for public. Changes in activity can also affect the people’s sense of place perception. This research strategy used is a mixed method that combines qualitative and quantitative research. Quantitative data through questionnaires were analyzed with cross tabulation techniques and qualitative data with literature studies and in-depth interviews which were then triangulated to obtain the final synthesis of research. The results show that the change has a positive effect on the inhabitant’s sense of place in term of activity. The sense of place itself is closely related to the level of community participation and sustainability in kampung development. This research has an important contribution to the development of the sense of place’s theory which can be a direction for the trilogy of settlement development such as government, private parties and local communities in determining the concept of sustainable tourism village development, especially in the city of Surabaya